Enhanced climate information services and big data solutions to enhance smallholder production for value chains in West Africa - Project Flyer - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This project aims to use Artificial Intelligence and associated technologies (Internet of Things IoT, Earth Observation, hyperlocal data streams) to enhance the impact of climate information by properly embedding it inside phygital value chain orchestration platforms that support equitable, multi-partner and multiscale business planning. The project focuses on Ghana, Nigeria and Senegal where it leverages the NADiRA H2020 innovation action on Nurturing Africa’s Digital Revolution for Agriculture, the CASCAID project on Capacitating African Stakeholders with Climate Advisories and Insurance Development, and the AIMS Mathematical Sciences for Climate Resilience (MS4CR) program. It relies on the agCelerant platform to safely connect smallholders to agro-industry, financial and input services and consumer markets. agCelerant solutions are rated market-ready, noteworthy for market creation potential by the EU Innovation Radar, and their development is supported by CCAFS.